Peran Serta Strategi Sistem Informasi Terhadap Keberhasilan Penerapan Teknologi Informasi Perusahaan - Oktavia, Tanty (ComTech: Computer, Mathematics and Engineering Applications, 2011)
The role and strategy of information sytems in all business sectors that exist at present have a very important priority for the company. This is inevitable because the information system has become an important part in the continuity of a company. Perhaps without the information system, the company’s operations will not be able to work properly because various sectors/divisions rely on business automation process. Planning strategy in an enterprise information system aims to enable companies to determine appropriate strategies in the information system implementation. Setting the information system and information technology strategically needs a way to understand the role of information technology on an organization. Most organizations will not hesitate to review the investment in information technology that has been done because the success of a company is also determined by the application of information systems. Evaluation of experience, success, and failure of the previous application is an important aspect in management strategy.